2007
DOI: 10.1158/1055-9965.epi-06-0914
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Colon Cancer Risk Counseling for First-Degree Relatives

Abstract: Background: Individuals with a first-degree relative who has had colorectal cancer are at increased risk for colorectal cancer and thus can benefit from early detection. Tailored risk counseling may increase adherence to screening guidelines in these persons. The present study evaluated a culturally sensitive Colon Cancer Risk Counseling (CCRC) intervention for relatives of colorectal cancer patients. Methods: A randomized trial evaluated personalized CCRC sessions with print materials and follow-up phone call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 35 publications
3
62
2
Order By: Relevance
“…Due to recruitment taking longer than anticipated, we also had to terminate recruitment prior to reaching our target sample size. The consent rate was similar to Glanz et al 13 using a similar registry‐based recruitment method to contact FDRs. The loss to follow‐up at 12 months was 21% and was similar for the intervention and control groups; however, the overall sample obtained was smaller than planned, which resulted in the detectable difference being larger than anticipated.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Due to recruitment taking longer than anticipated, we also had to terminate recruitment prior to reaching our target sample size. The consent rate was similar to Glanz et al 13 using a similar registry‐based recruitment method to contact FDRs. The loss to follow‐up at 12 months was 21% and was similar for the intervention and control groups; however, the overall sample obtained was smaller than planned, which resulted in the detectable difference being larger than anticipated.…”
Section: Discussionsupporting
confidence: 53%
“…Our outcome takes into account the potential for screening intervention to result in inappropriate increases in screening, and as such, may provide a better indication of the usefulness of the intervention. Glanz et al 13 used similar recruitment and had similar numbers of FDRs in their risk categories and found that face‐to face and telephone counselling was effective in improving CRC screening adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review represents data on the reports of RCTs that used decision support tools in minority populations (Table 2). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Two of the articles described different outcomes from one RCT. 31,32 Thus, we considered these two papers one intervention, resulting in a total of 18 interventions with data.…”
Section: Resultsmentioning
confidence: 99%
“…The authors used counseling, print materials, and phone calls to deliver decision support. 23 Counseling sessions were led by a nurse or health educator, and were tailored to the diverse and multiethnic population of Hawaii. The study aimed to increase colorectal screening among children and siblings of CRC patients.…”
Section: Decision Aid Type and Deliverymentioning
confidence: 99%